The importance of agricultural objectives : summary of studies - Ahtiainen, Heini; Pouta, Eija; Liski, Eero; Assmuth, Aino; Myyrä, Sami (European Association of Agricultural Economists (EAAE), 2014)
This paper summarizes information on the importance of the objectives of agriculture and agricultural policies based on previous studies. We focus on studies that examine stakeholder preferences and provide relative weights for the economic, social and environmental dimensions of sustainability. Descriptive and meta-analysis are used to evaluate the 34 identified studies. The findings show the equal importance of the economic, social and environmental objectives of agriculture, but also that the general public emphasizes social values, while economic considerations are highlighted in nation-wide studies. Of the environmental objectives, those pertaining to sustainable resource management have received most weight.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; multifunctionality; objektives; agriculture; sustainability; weighting